EVALUATION OF CHEMISTRY LEARNING VIDEOS FROM ONLINE LEARNING APPLICATIONS IN INDONESIA - Muhammad Reza; Nurmalahayati Nurdin; Naila Naila; Wilda Puspita Sari (Chimica Didactica Acta, 2023)
E-learning is not distinct from the use of technology, which includes a variety of digital platforms. Zenius, Ruangguru, Pahamify, and other online learning systems are currently available in Indonesia. There are various learning films on the learning platform, such as on the applications B and C, which both give a variety of features and materials that complement the curriculum K-13, particularly in chemistry. The qualitative descriptive methodologies were used in this investigation. The purpose of this research is to compare the quality of chemistry learning resources available on online learning applications that correspond to the 2013 curriculum. Data is gathered through the downloading and video monitoring of chemical compounds. Two learning apps, B and C, were utilized as examples. According to the findings of this study, application B has a bigger number of videos in the material than application C. In addition, the average video time on the B app is less topical than on the C app. A good learning video has an appropriate length. When the video is too long, the spectator becomes bored. The video's attributes should be clear, and a pleasant appearance, such as animation, can encourage students to follow.